The impact of digital games and virtual reality on behavioral disorders in children, in the kingdom of Bahrain - Layla Abdarasool Hussein; Nadia Mohamed Mahmoud; Hossam Elhamy (المجلة الدولية للحاسبات والمعلوماتية, 2024)
The current study presents a pivotal and fundamental issue in the field of digital games and virtual reality in particular in the kingdom of bahrain and its impact on behavioral disorders in children, and it aimed to identify the effects of children's use of these digital games and virtual reality and their negative or positive impact on their behaviors. Where the descriptive survey approach was used, and we were selected for a sample represented by all parents, which is a comprehensive sample consisting of (338) single parents in the kingdom of bahrain, who were randomly selected from them (198) males and (140) females by choosing (questionnaire method) in the analysis of the study (and personal interviews). With some people in a selected way, the study found that digital games and virtual reality have a significant impact on children's behaviors negatively, and the study recommended concerned parents and the media to educate children about the importance of digital games and the virtual world, and the dangers of playing these games for a long time.